Stress during the covid-19 pandemic: unusual challenges for university professors - Maria Neyrian de Fatima Fernandes; Floriacy Stabnow Santos; Ana Cristina Pereira de Jesus Costa; Marcelino Santos Neto; Roberta de Araújo e Silva; Leonardo Hunaldo dos Santos (Medicina, 2023)
Objective: Investigate the factors related to the stress levels triggered during the COVID-19 pandemic and the quality of life (QOL) of university professors. Methods: This is a cross-sectional study with 318 professors from private and public higher education institutions in Maranhão, Brazil. Data collection included a sociodemographic questionnaire, the Brazilian versions of the Perceived Stress Scale (PSS), and the Abbreviated World Health Organization QOL Assessment Instrument (WHOQOL-bref). Statistical analyses were performed with Student’s T-test and Analysis of Variance with Duncan’s post-hoc. Results: according to the results of the professor score assessment, perceived stress levels were classified as normal (n = 166, 52.2%), moderate (n = 126, 39.6%), and high (n = 26, 8, 2%), with an average of 26.6 (± 10.5). QOL had an overall average of 56.4 (± 13.0). Among the QOL domains, the physical had the highest mean with 66.1 (± 17.7), while the lowest mean was in the social domain with 55.8 (± 14.8). Conclusion: The factors that influenced the stress levels were being female with age between 31 and 40 years old, those who had a child, and those who did not perform a frequent religious practice.